Manajemen Lembaga Pendidikan Nonformal dalam Mengimplementasikan Kebijakan Asesmen Nasional di PKBM Budi Utama Kota Surabaya - Nurcahyani, Dina; Widodo, Widodo (J+PLUS UNESA, 2023)
The problem in this research is that the National Assessment policy is a policy that has just been launched to improve the quality of education as an educational institution CLC Budi Utama must also take a role in implementing the policy. As an institution that has good accreditation, CLC Budi Utama will be careful in preparing and implementing this new policy so that management is needed that can succeed and maximize the course of the National Assessment. The purpose of this study is to find out how the implementation of the management function which includes planning, organizing, implementing, and supervising the implementation of AN policy with qualitative methods. The subjects of this study were CLC directors, institutional staff, exam committees, and AN participants. Data collection techniques using in-depth interviews, observation, and documentation. The techniques used in data analysis are data reduction, data presentation and verification. After that tested the truth value using triangulation techniques. The results of this study indicate that the management function in implementing AN policy is based on theory which includes planning, organizing, implementing, and supervising.